Hubungan Pengetahuan dan Sikap Pasangan Usia Subur dalam Alat Kontrasepsi Dalam Rahim - Syifa Fathiyatu Diyanah; Is Susiloningtyas; Emi Sutrisminah (Jurnal Maternitas Kebidanan, 2022)
Long-term highly effective reversible contraceptive methods have historically increased in popularity and declined in different regions of the world. The decrease in the number of AKDR participants every year is due to several factors, one of which is ignorance about the advantages of contraceptives in the womb where knowledge and attitudes in choosing contraception become influential considerations in determining the method of contraception to be used. This review literature aims to conduct a review of the articles of research results over the past 10 years to find out the relationship of knowledge and attitudes of Couples of Childbearing Age in the use of Intraute Contraceptives especially IUDs. Methods used with foreign and local review literature are searched through electronic media online and use Google scholar, Sinta, and Pubmed data base using keywords. The results showed that there is a relationship between knowledge and attitudes of Couples of Childbearing Age in using Intrauteute Contraceptives. The conclusion of this study is that there is a relationship between knowledge and attitudes of Couples of Childbearing Age in the use of Contraceptives in the Womb